2009
DOI: 10.1371/journal.pgen.1000348
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatic Threads Connect Oscillating Chromosomes during Prometaphase I in Drosophila Oocytes

Abstract: In Drosophila oocytes achiasmate homologs are faithfully segregated to opposite poles at meiosis I via a process referred to as achiasmate homologous segregation. We observed that achiasmate homologs display dynamic movements on the meiotic spindle during mid-prometaphase. An analysis of living prometaphase oocytes revealed both the rejoining of achiasmate X chromosomes initially located on opposite half-spindles and the separation toward opposite poles of two X chromosomes that were initially located on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 33 publications
5
106
0
Order By: Relevance
“…These tethers appear to be built from pericentromeric heterochromatin and are proposed to establish tension between chromosomes not held together by chiasmata, thus allowing homologous coorientation to be established (Hughes et al 2009(Hughes et al , 2011. Similar tethers have been inferred by micromanipulation experiments in grasshopper spermatocytes (LaFountain et al 2002) and by PICH localization to DNA threads connecting mitotic sister kinetochores in mammalian cultured cells (Baumann et al 2007).…”
mentioning
confidence: 62%
“…These tethers appear to be built from pericentromeric heterochromatin and are proposed to establish tension between chromosomes not held together by chiasmata, thus allowing homologous coorientation to be established (Hughes et al 2009(Hughes et al , 2011. Similar tethers have been inferred by micromanipulation experiments in grasshopper spermatocytes (LaFountain et al 2002) and by PICH localization to DNA threads connecting mitotic sister kinetochores in mammalian cultured cells (Baumann et al 2007).…”
mentioning
confidence: 62%
“…In wild-type Drosophila oocytes, 6-12% of normal X chromosome bivalents fail to recombine and therefore belong to the E 0 tetrad exchange rank (Ashburner 1989;Zwick et al 1999 Reduced centromere-proximal heterochromatin contributes to age-dependent NDJ of achiasmate chromosomes in ord 4 /ord 10 oocytes: In addition to promoting arm cohesion and meiotic exchange, ORD also functions at the centromere and is highly enriched at pericentric heterochromatin (see Figure 1). Homologous pairing of centromere proximal heterochromatin is essential for proper achiasmate chromosome disjunction in Drosophila oocytes Hawley and Theurkauf 1993;Karpen et al 1996) and this pairing is maintained until anaphase I (Dernburg et al 1996;Gilliland et al 2009;Hughes et al 2009). One possibility is that the FM7a chromosome is more vulnerable to increased NDJ in aged ord 4 /ord 10 oocytes because a large portion of the pericentric heterochromatin is displaced to the distal end of the chromosome ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is a linear relationship between the amount of pericentric heterochromatin and the fidelity of achiasmate segregation (Karpen et al 1996). Cytological analyses of Drosophila oocytes indicate that the centromere-proximal heterochromatin of homologous chromosomes remains associated from pachytene until anaphase I (Dernburg et al 1996;Gilliland et al 2009;Hughes et al 2009). However, whether or how specific heterochromatin proteins promote this association has not been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(C) As shown by Hughes et al [35], achiasmate homologs can be found on the same side of the metaphase plate. This is the irst demonstration that this coniguration can occur, and it suggests that achiasmate homologs can move in unison.…”
Section: Chromosomal Abnormalities -A Hallmark Manifestation Of Genommentioning
confidence: 63%